The Sociological Study of Ethnocentrism in Iranian Azerbaijan from the Pan-Turkists' Point of View - Shaban Mohammadi; ahmad rezaee (توسعه اجتماعی, 2019)
The present research paper examines the tendency towards Pan-Turkism in Iranian Azerbaijan from the Pan-Turkists' point of view. In Gajar era, Iranian Azeris regarded themselves as pure Iranians and defended Iran's northwest borders. The formation of authoritarian Pahlavi government in the twentieth century helped to change this positive attitude towards the Iranian central government. Our methodology is a qualitative and we used the ethnography, observation, and deep interview to collect the data. The findings were the following categories: structural determent, interaction, attitudes towards the national identity, authoritarian government, cultural deprivation, economic deprivation, political deprivation, media insult, and Pan-Turkism.